Economic Empowerment through the Production of Fish Pellet, Organic Fertilizers from Maggots, and Catfish Nuggets from Budikdamber in Kronggahan Hamlet, Gamping, Sleman - Sarastuti, Dewi; Suwito, Darwito; Budiyanto, Arief; Puspitasari, Ika; Alchusnah, Retno Hayati; Yusmiyati, Yusmiyati; Purnomo, Chandra Wahyu (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Sleman Regency produces the biggest waste pile, approximately 701.95 tons/day, higher than the other districts in Yogyakarta Province (The Ministry of Environment and Forestry, 2020). National data show that unmanaged waste is 12.4% per year. This unmanaged waste has the potential to cause significant environmental and health problems. Efforts to minimize organic waste have been carried out by Kronggahan residents by utilizing waste bioconversion technology with black soldier fly (BSF) technology to produce maggot and kasgot. Maggot could be used for feeding fish and kasgot could be used for plant fertilizers. Kronggahan Hamlet has also developed several activities such as the, the development of aquaponics and budikdamber (budidaya ikan dalam ember-farming fish in buckets) where the feeding of catfish use maggot’s product. Harvested catfish and spinach from aquaponics and budikdamber can be processed into nuggets and could be added value for food security in Kronggahan Hamlet. This technology reduce organic waste by ± 70% by converted it into alternative fish feed that has economic value and high nutritional content. The purpose of this community empowerment activity was to increase community knowledge about maggot and maggot product proccessing from organic waste, foster knowledge in maintaining and improving health to prevent non communicable diseases. Hopefully, stakeholder can adopt policies in processing organic waste into maggot, the public can apply organic waste treatment and play a role in reducing the organic waste produced. The methods of implementing this program encompassed knowledge sharing, coordination and consolidation, preparation of educational media, and training packages that were integrated with other productive economic activities facilitated by Academic Hospital UGM’s community empowerment team in collaboration with Kronggahan Hamlet residents. Hopefully this program will be able to be publicized more broadly and can be duplicated in other regions.